The association of neutrophil to lymphocyte ratio with presence and severity of obstructive sleep apnea - (:unkn) unknown (COMENIUS UNIV, 2015)
BACKGROUND: Obstructive sleep apnea (OSA) is characterized by reductions in breathing amplitude during sleep caused by an obstructed or collapsed upper airway. The neutrophil to lymphocyte ratio (NLR) has been proposed as a novel biomarker for systemic inflammatory response. The aim of the present study was to evaluate the relationship between NLR and OSA. METHODS: The study population consisted of 195 consecutive patients with clinical suspicion of OSA. Full night polysomnography was performed for all patients. Patients with an apnea hypopnea index (AHI) 5 were considered to have OSA. NLR was calculated as the ratio of neutrophil count to lymphocyte count. RESULTS: While 130 patients (91 male, mean age: 49.9 +/- 9.8 years) had OSA, 65 patients (42 male, mean age: 48.7 +/- 10.2 years) had normal findings according to AHI scores. Cardiovascular risk factors such as hypertension, hyperlipidemia, diabetes mellitus and smoking were more common in patients with OSA. Patients with OSA had significantly higher NLR than controls (1.87 +/- 0.80 vs 1.49 +/- 0.48, p=0.005). AHI score was significantly correlated with NLR (r=0.228, p=0.001). NLR and presence of hyperlipidemia were independent predictors of OSA (OR: 2.451, 2.850, p=0.001, 0.004, respectively). NLR of 1.62 or higher predicted OSA with a sensitivity of 56.2 % and specificity of 63.1 %. CONCLUSIONS: NLR was higher and also correlated with AHI score in patients with OSA which has not been reported previously. NLR more than 1.62 was an independent predictor of OSA. A simple, cheap white blood cell count may also give an idea about the presence and severity of OSA (Tab. 3, Fig. 3, Ref. 30). Text in PDF www.elis.sk.
Keywords: inflammation; cardiovascular risk; neutrophil to lymphocyte ratio; obstructive sleep apnea; C-REACTIVE PROTEIN; CARDIOVASCULAR-DISEASE; INFLAMMATION